MASYARAKAT DESA BERBASIS INTEGRATED FARMING SYSTEM: ASURANSI SYARIAH PADA BIDANG PERTANIAN - Muhammad Askari Zakariah, Muhammad Askari; Zakariah, M; Rismayani, Rismayani (Syari'ah, 2017)
Impact of green house gases is damage to environment, one result of that has been felt with increasing temperature of the earth surface that could eventually lead to extreme climate change. Climate change is expected to have an impact on agriculture production throughout the world. Government have to serve program to assure agriculture production. Shariah assurance of agriculture as social care movement without uncertainly, debt, gambling, and bank interest. Ministry of agriculture has released regulation Nomor 40 Tahun 2015, on this regulation was arranged types and facility agriculture assurance will protect farmers from losses profit because failed in harvesting because disaster act of god, diseases, and climate extreme change. In these regulation, any word containing shariah point, we do hope agriculture assurance can be operated in form shariah skim.